Analysis of Digital Marketing Utilization for MSMEs in Dayeuhluhur District - Susila, Eka; Yulianti, Laila; Pratminingsih, Sri Astuti . (CENTRAL ASIA AND THE CAUCASUS, 2022)
The challenges of MSMEs as the spearhead of the country's economy due to the flow of globalization and the rapid advancement of information technology coupled with the Covid-19 pandemic that occurred, required a breakthrough in the field of marketing digitalization to reach a wide market and maintain the sustainability of the MSME economy. This study aims to determine the extent to which the implementation of the use of digital marketing in MSMEs in Dayeuhluhur district can be applied. The method in this research is descriptive qualitative with data collection techniques using in-depth interviews and field observations of MSME actors in the Dayeuhluhur sub-district. Data analysis and processing is carried out through the process of data reduction, data presentation, and conclusion drawing.